2010
DOI: 10.1111/j.1432-2277.2010.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant alterations following donation after cardiac death donor lungs

Abstract: Summary The use of lungs from donation after cardiac death (DCD) donors is one of the strategies to increase the donor pool. The aim of this study was to assess the surfactant alterations in DCD donor lungs. Pigs were sacrificed and left untouched for 1 (DCD1), 2 (DCD2) and 3 (DCD3) h. Lungs were then topically cooled with saline for 1, 2 or 3 h to reach a total ischemic time of 4 h. Heart‐beating donors (HBD) served as control group. Bronchoalveolar lavage (BAL) samples were assessed for protein levels and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…This was proven by significantly different adsorption and surface tension in DCD groups compared with heart-beating donor (HBD) group (49).…”
Section: Proof Of Concept and Experimental Backgroundmentioning
confidence: 97%
See 1 more Smart Citation
“…This was proven by significantly different adsorption and surface tension in DCD groups compared with heart-beating donor (HBD) group (49).…”
Section: Proof Of Concept and Experimental Backgroundmentioning
confidence: 97%
“…To assess the surfactant alterations in DCD donor lungs (49) we showed that surfactant function decreases with increased WITs. This was proven by significantly different adsorption and surface tension in DCD groups compared with heart-beating donor (HBD) group (49).…”
Section: Proof Of Concept and Experimental Backgroundmentioning
confidence: 99%
“…Inhaled nitric oxide and beta-adrenergic drugs were used in different studies. Another utilization of inhalation treatments is the one concerning surfactant (4,30). Anti-inflammatory drugs, antiapoptotic drugs, antibiotics, and immunosuppressants are added to the perfusate for treatment purposes.…”
Section: Examples For Study Methodsmentioning
confidence: 99%
“…For this procedure, 5 mL/ kg betaine HCL/pepsin was bronchoscopically instilled (24). Another application of EVLP is to assess organs of NHBD (30,31). This is why, death before harvesting should be initiated in the experimental setup.…”
Section: Injurymentioning
confidence: 99%
“…Warm ischemia is the ischemia of cells and tissues under normothermic conditions. It leads to endothelial dysfunction and to alveolar type II cell dysfunction resulting in pulmonary edema and graft dysfunction during reperfusion [6][7][8][9]. There is experimental and clinical evidence that 1 h of WI does not compromise the function of the pulmonary graft [10].…”
Section: Introductionmentioning
confidence: 99%